Carbon resistance of xNi/HTASAO5 catalyst for the production of H2 via CO2 reforming of methane. (11th June 2021) - Cui, Chaojun; Wang, Ye; Du, Xiangze; Li, Li; Song, Mouxiao; Zeng, Wenqing; Li, Guiying; Hu, Changwei
Abstract: xNi/HTASAO5 catalysts (x = 2.5, 3.3, 4.4, 5.8, 8.2) were prepared for CO2 reforming of methane. No crystalline nickel species formed on the catalysts with lower nickel content (≤4.4%), and large Ni 0 crystallite formed on 5.8% (10 nm) and 8.2 wt%Ni/HTASAO5 (17 nm), whereas the surface concentration of Ce 3+ decreased with Ni loading. The initial conversion of CH4 increased from 29.5% to 46.9% with Ni loading. The xNi/HTASAO5 (x ≤ 4.4%) performed stably in the reaction due to the presence of dispersed Ni species and high surface Ce 3+ content without coke formation, however, 5.8% and 8.2 wt%Ni/HTASAO5 exhibited decreased activity with time on stream, because of the formation of large Ni particles with lower surface Ce 3+, leading to carbon accumulation. Thus, CH4 conversion stabilized at about 43% and no carbon formed on 4.4 wt%Ni/HTASAO5 with optimum Ni loading. Graphical abstract: 4.4 wt%Ni/HTASAO5 exhibited high activity and stability in DRM reaction with no coke formation. Image 1 Highlights: CH4 conversion stabilized at 43% on 4.4 wt%Ni/HTASAO5 in DRM reaction at 600 °C. No carbon deposited on the spent catalysts with no crystallite of Ni 0 . Ce 3+ concentration and adsorbed oxygen increases with decreasing Ni loading. Reverse water gas shift reaction and carbon removal promoted by surface Ce 3+ . The content of medium - strength basic sites increases with decreasing Ni loading.